Faktor-faktor yang Berkontribusi terhadap Kepemilikan Sertifikasi Usaha di Kalangan Peserta Pelatihan UMKM di Jawa Timur - Aminudin, Muhammad Sulton (Cendekia Niaga, 2025)
This study aims to analyze the influence of the education of business owner, type of business, business turnover, and number of employees on the ownership of a Business Identification Number (NIB) in Micro, Small, and Medium Enterprises (MSMEs) of East Java Province. Data gathered from 1,041 MSMEs and the binary logistik regression method, that found simultaneously the variabels of education, type of business, and turnover had a significant effect on NIB ownership, while the number of employees was not significant either simultaneously or per category. Specifically, education had a collective effect but there was no particular level of education that individually significantly increased the chances of having a NIB. The type of business was the most consistent factor: MSMEs in the handicraft, fashion, and food/beverage sectors had a significantly higher chance of having a NIB than other sectors. Turnover had a significant effect simultaneously, but no particular turnover category was found to individually increase the chances of having a NIB. The number of employees did not show a significant effect on NIB ownership, either simultaneously or in each category. This finding confirms that the strategy of increasing business legality through NIB in MSMEs is more effective if it is focused on education and mentoring of potential business sectors, not solely based on turnover or number of employees. This study provides policy implications so that government intervention is more directed at strengthening access to information, legal assistance, and business sectors that empirically need more formal legality.